Molt-dependent transcriptomic analysis of cement proteins in the barnacle Amphibalanus amphitrite. (December 2015) - Wang, Zheng; Leary, Dagmar; Liu, Jinny; Settlage, Robert; Fears, Kenan; North, Stella; Mostaghim, Anahita; Essock-Burns, Tara; Haynes, Sarah; Wahl, Kathryn; Spillmann, Christopher
Abstract Background A complete understanding of barnacle adhesion remains elusive as the process occurs within and beneath the confines of a rigid calcified shell. Barnacle cement is mainly proteinaceous and several individual proteins have been identified in the hardened cement at the barnacle-substrate interface. Little is known about the molt- and tissue-specific expression of cement protein genes but could offer valuable insight into the complex multi-step processes of barnacle growth and adhesion. Methods The main body and sub-mantle tissue of the barnacleAmphibalanus amphitrite (basionymBalanus amphitrite ) were collected in pre- and post-molt stages. RNA-seq technology was used to analyze the transcriptome for differential gene expression at these two stages and liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) was used to analyze the protein content of barnacle secretions. Results We report on the transcriptomic analysis of barnacle cement gland tissue in pre- and post-molt growth stages and proteomic investigation of barnacle secretions. While no significant difference was found in the expression of cement proteins genes at pre- and post-molting stages, expression levels were highly elevated in the sub-mantle tissue (where the cement glands are located) compared to the main barnacle body. We report the discovery of a novel 114kD cement protein, which is identified in material secreted onto various surfaces by adult barnacles and with the encoding gene highly expressed in the sub-mantle tissue. Further differential gene expression analysis of the sub-mantle tissue samples reveals a limited number of genes highly expressed in pre-molt samples with a range of functions including cuticular development, biominerialization, and proteolytic activity. Conclusions The expression of cement protein genes appears to remain constant through the molt cycle and is largely confined to the sub-mantle tissue. Our results reveal a novel and potentially prominent protein to the mix of cement-related components inA. amphitrite . Despite the lack of a complete genome, sample collection allowed for extended transcriptomic analysis of pre- and post-molt barnacle samples and identified a number of highly-expressed genes. Our results highlight the complexities of this sessile marine organism as it grows via molt cycles and increases the area over which it exhibits robust adhesion to its substrate.